Deletion of TNFAIP6 Gene in Human Keratinocytes Demonstrates a Role for TSG-6 to Retain Hyaluronan Inside Epidermis - Céline Evrard; Emilie Faway; Evelyne De Vuyst; Olivier Svensek; Valérie De Glas; David Bergerat; Michel Salmon; Olivier De Backer; Bruno Flamion; Hélène Le-Buanec; Catherine Lambert de Rouvroit; Yves Poumay (Elsevier, 2021)
TSG-6 is a soluble protein secreted in the extracellular matrix by various cell types in response to inflammatory stimuli. TSG-6 interacts with extracellular matrix molecules, particularly hyaluronan (HA), and promotes cutaneous wound closure in mice. Between epidermal cells, the discrete extracellular matrix contains HA and a tiny amount of TSG-6. However, challenges imposed to keratinocytes in reconstructed human epidermis revealed strong induction of TSG-6 expression, after exposure to T helper type 2 cytokines to recapitulate the atopic dermatitis phenotype or after fungal infection that causes secretion of cytokines and antimicrobial peptides. After both types of challenge, enhanced release of TSG-6 happens simultaneously with increased HA production. TSG-6 deficiency in N/TERT keratinocytes was created by inactivating TNFAIP6 using CRISPR/Cas9. Some TSG-6-/- keratinocytes analyzed through scratch assays tend to migrate more slowly but produce reconstructed human epidermis that exhibits normal morphology and differentiation. Few significant alterations were noticed by transcriptomic analysis. Nevertheless, reduced HA content in TSG-6-/- reconstructed human epidermis was observed, along with enhanced HA release into the culture medium, and this phenotype was even more pronounced after the challenging conditions. Reintroduction of cells producing TSG-6 in reconstructed human epidermis reduced HA leakage. Our results show a role for TSG-6 in sequestering HA between epidermal cells in response to inflammation.